Workshop on ACD MBA Programme for ACD University Network: A Report. - Ansary, Ahmed (2019)
The Asia Cooperation Dialogue (ACD) is a multilateral organisation consisting of 35 Asian Countries; the Islamic Republic of Afghanistan, the Kingdom of Bahrain, the People’s Republic of Bangladesh, the Kingdom of Bhutan, Brunei Darussalam, the Kingdom of Cambodia, the People’s Republic of China, the Republic of India, the Republic of Indonesia, the Islamic Republic of Iran, Japan, the Republic of Kazakhstan, the Republic of Korea, the State of Kuwait, the Kyrgyz Republic, the Lao People’s Democratic Republic, Malaysia, Mongolia, the Republic of the Union of Myanmar, Federal Democratic Republic of Nepal, the Sultanate of Oman, the Islamic Republic of Pakistan, the Republic of the Philippines, the State of Qatar, the Russian Federation, the Kingdom of Saudi Arabia, the Republic of Singapore, the Democratic Socialist Republic of Sri Lanka, the Republic of Tajikistan, the Kingdom of Thailand, the Republic of Turkey, the United Arab Emirates, the Republic of Uzbekistan, the Socialist Republic of Viet Nam, and the State of Palestine.